2018
DOI: 10.3390/f9020079
|View full text |Cite
|
Sign up to set email alerts
|

Renewable Energy from Forest Residues—How Greenhouse Gas Emission Offsets Can Make Fossil Fuel Substitution More Attractive

Abstract: Burning forest biomass from renewable sources has been suggested as a viable strategy to help offset greenhouse gas (GHG) emissions in the energy generation sector. Energy facilities can, in principle, be retrofitted to produce a portion of their energy from biomass. However, supply uncertainties affect costs, and are an important impediment to widespread and sustained adoption of this strategy. In this paper, we describe a general approach to assess the cost of offsetting GHG emissions at co-generation facili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 47 publications
1
7
0
1
Order By: Relevance
“…Further sources of forest biomass are sought; for example, forest undergrowth is harvested and processed into pellets [9]. An additional factor favoring various types of forest residue biomass for heat and electricity production is the opportunity to offset greenhouse gas emissions, which could make biomass use more economically viable [10].…”
Section: Introductionmentioning
confidence: 99%
“…Further sources of forest biomass are sought; for example, forest undergrowth is harvested and processed into pellets [9]. An additional factor favoring various types of forest residue biomass for heat and electricity production is the opportunity to offset greenhouse gas emissions, which could make biomass use more economically viable [10].…”
Section: Introductionmentioning
confidence: 99%
“…The development of local district energy system represents one potential way to reduce heating costs especially in remote off‐grid communities and allowing for important savings on the costs associated with transporting biomass over long distances (Stephen et al, ) Utilizing biomass in an innovative manner and factoring in the cost of GHG substitution may also bring new insights and added incentives. If the market for GHG emission offsets is established with a competitive price, the benefits of offsetting GHG emissions could be factored into the cost of salvaging woody biomass for bioenergy, making the required investment more profitable (Yemshanov, McKenney, Hope, & Lempriere, ).…”
Section: What Are the Constraints In Developing An Integrated Supply mentioning
confidence: 99%
“…Forest residues are a sustainable source of bioenergy, involving the use of a by-product to replace fossil fuel alternatives, with the potential to lead to GHG emission savings [21]. Recent international studies have explored forest residue bioenergy and found several possible benefits, including emission reductions, and regional development opportunities in northern Spain [22], northern Italy [23], Canada [24], and the United States [25].…”
Section: Introductionmentioning
confidence: 99%